Selected contribution: Peripheral chemoreflex function in high-altitude natives and patients with chronic mountain sickness. - Léon-Velarde, F; Gamboa, A; Rivera-Ch, M; Palacios, J; Robbins, P (2003)
Peripheral chemoreflex function was studied in high-altitude (HA) natives at HA, in patients with chronic mountain sickness (CMS) at HA, and in sea-level (SL) natives at SL. Results were as follows. 1) Acute ventilatory responses to hypoxia (AHVR) in the HA and CMS groups were approximately one-third of those of the SL group. 2) In CMS patients, some indexes of AHVR were modestly, but significantly, lower than in healthy HA natives. 3) Prior oxygenation increased AHVR in all subject groups. 4) Neither low-dose dopamine nor somatostatin suppressed any component of ventilation that could not be suppressed by acute hyperoxia. 5) In all subject groups, the ventilatory response to hyperoxia was biphasic. Initially, ventilation fell but subsequently rose so that, by 20 min, ventilation was higher in hyperoxia than hypoxia for both HA and CMS subjects. 6) Peripheral chemoreflex stimulation of ventilation was modestly greater in HA and CMS subjects at an end-tidal Po(2) = 52.5 Torr than in SL natives at an end-tidal Po(2) = 100 Torr. 7) For the HA and CMS subjects combined, there was a strong correlation between end-tidal Pco(2) and hematocrit, which persisted after controlling for AHVR.